2010
DOI: 10.1111/j.1365-3024.2009.01179.x
|View full text |Cite
|
Sign up to set email alerts
|

Enalapril prevents cardiac immune-mediated damage and exerts anti-Trypanosoma cruziactivity during acute phase of experimental Chagas disease

Abstract: Chagas heart disease (CHD), caused by Trypanosoma cruzi infection, is a significant cause of morbidity and mortality in South and Central America. Enalapril, an angiotensin converting enzyme (ACE) inhibitor, is an important drug used to ameliorate heart functional capacity and its remodelling in individuals presenting CHD. In this study, we evaluated the effects of enalapril on systemic and cardiac immune response during experimental acute CHD. C57BL/6 mice infected with 50 trypomastigote forms of T. cruzi (Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 28 publications
(29 reference statements)
0
29
0
Order By: Relevance
“…Therefore, cardiovascular drugs that are routinely used (e.g., ACE inhibitors, beta-blockers and others) have been tested for the treatment of Chagas disease. With a new anti-inflammatory focus, studies have demonstrated a drastic reduction in leukocyte infiltration in the heart, fibrosis, circulating inflammatory cytokines/chemokines and improvements in cardiac output ventricular functions in Chagas disease (Morris et al 1989, Leon et al 2003, Botoni et al 2007, Coelho dos , Paula-Costa et al 2010. Because of these results, new therapeutic targets based on statins, a lipid-modifying agent HMG-CoA, have emerged as a method to prevent cardiovascular diseases (Liao 2002, Cheng et al 2005, Mizuno et al 2011.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, cardiovascular drugs that are routinely used (e.g., ACE inhibitors, beta-blockers and others) have been tested for the treatment of Chagas disease. With a new anti-inflammatory focus, studies have demonstrated a drastic reduction in leukocyte infiltration in the heart, fibrosis, circulating inflammatory cytokines/chemokines and improvements in cardiac output ventricular functions in Chagas disease (Morris et al 1989, Leon et al 2003, Botoni et al 2007, Coelho dos , Paula-Costa et al 2010. Because of these results, new therapeutic targets based on statins, a lipid-modifying agent HMG-CoA, have emerged as a method to prevent cardiovascular diseases (Liao 2002, Cheng et al 2005, Mizuno et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Even with a significant reduction in the levels of inflammatory mediators, such as IFN-γ and TNF-α, 30-40% mortality was expected in mice during peak parasitaemia based on the biological characteristics of the Colombian strain in isogenic C57BL/6 mice (Talvani et al 2000, Paula-Costa et al 2010. Unfortunately, mice do not survive well due to the alterations in the metabolic pathways that are a result of a persistent inflammatory response induced by specific strains of T. cruzi (Sánchez-Guillén et al 2006), which is a limitation of this experimental model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4] Since the presence of T. cruzi is the switch for inducing and maintaining the inflammatory process running in the heart tissue, three cardinal therapeutic strategies are proposed: 1) an antiparasitic drug, where benznidazole is considered a standard treatment but still ineffective to those symptomatic individuals in chronic stage of Chagas cardiopathy 5 ; 2) drugs that act direct on the cardiac dysfunction avoiding progressive failure of the organ-for example, diuretics, digitals, β-blockers, and angiotensin-converting enzyme (ACE) inhibitors 6,7 and, more recently, 3) drugs that act in controlling the over-reactivity of the immune system avoiding severe destruction in the heart during chronic stage of the infection-for example, statins and ACE inhibitors. [8][9][10][11][12] ACE inhibitors have been shown to be efficacious not only as therapies against hypertension and protection against left ventricular hypertrophy but also in the regulation of the immune system related to distinct diseases, including the T. cruziinduced pathologies. 9,[13][14][15] Their actions are based on the angiotensin II, a key factor in the renin-angiotensin system that plays an essential role in the regulation of blood pressure, and that also interferes in the cardiac inflammatory activity through the activation of the nuclear factor kappaB (NF-κB) and in the production of inflammatory cytokines and chemokines.…”
Section: Introductionmentioning
confidence: 99%